1990
DOI: 10.1136/ard.49.8.587
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the single dose pharmacokinetics of sulphasalazine in rheumatoid arthritis and inflammatory bowel disease.

Abstract: The pharmacokinetics of sulphasalazine and its principal metabolites in rheumatoid arthritis (RA) and inflammatory bowel disease (IBD) were compared. Patients with RA had a significantly greater concentration of plasma sulphapyridine than patients with IBD (medians 140 tg/ml and 7-4 pg/mI respectively). Patients with RA also tended to maintain a higher plasma sulphapyridine concentration with time, as determined by the area under the curve (AUC), but a lower plasma sulphasalazine AUC than patients with IBD. It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

1991
1991
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 23 publications
0
9
1
Order By: Relevance
“…Plasma concentrations of sulphapyridine may be highly variable in patients with rheumatoid arthritis. Maximum concentrations ranged from 8 to 22 mglL after single 2g doses of sulphasalazine in 1 study (Astbury et al 1990). Mean (± SD) steady-state concentrations of 18 ± 20 mglL were reported in 12 older patients, and 15 ± 8 mglLin 8 younger patients after 17 days' administration of sulphasalazine 2 g/day .…”
Section: Concentration-effect Relationshipsmentioning
confidence: 89%
See 3 more Smart Citations
“…Plasma concentrations of sulphapyridine may be highly variable in patients with rheumatoid arthritis. Maximum concentrations ranged from 8 to 22 mglL after single 2g doses of sulphasalazine in 1 study (Astbury et al 1990). Mean (± SD) steady-state concentrations of 18 ± 20 mglL were reported in 12 older patients, and 15 ± 8 mglLin 8 younger patients after 17 days' administration of sulphasalazine 2 g/day .…”
Section: Concentration-effect Relationshipsmentioning
confidence: 89%
“…Estimates of about 10 to 30% absorption in the small intestine, with extensive enterohepatic recycling, have been reported (Khan & Truelove 1982;Lewkonia et al 1973;Pinals 1988). The terminal elimination half-life of sulphasalazine in groups of patients with rheumatoid arthritis and with inflammatory bowel disease ranged from 3 to 9 hours (Astbury et al 1990). Elimination half-life was prolonged in the elderly (Taggart et al , 1992.…”
Section: Overview Of Dispositionmentioning
confidence: 92%
See 2 more Smart Citations
“…A higher incidence of adverse reaction has been noted after treatment with sulfasalazine in adult rheumatoid arthritis than in inflammatory bowel disease (Astbury et al 1990; references therein). A comparative single-dose (sulfasalazine 2g) pharmacokinetic study by Astbury et al (1990) revealed significantly higher plasma concentrations of sulfapyridine but lower values for sulfasalazine in rheumatoid arthritis than in inflammatory bowel disease.…”
Section: Suljasalazinementioning
confidence: 97%